Psychopharmacology : a concise overview - Ansari, Arash; Osser, David N. (David Neal) (New York, NY : Oxford University Press, 2020)
Psychopharmacology: A Concise Overview, Third Edition is an evidence-based overview of the major classes of psychiatric medications and their use in clinical practice. Clinical considerations as to when, why, and how to use each individual medication are discussed in depth, as are relevant clinical controversies and treatment caveats. Each chapter also features an updated table of individual medications and their generic and brand names, dosing information, pertinent clinical comments, black box warnings, and Food and Drug Administration indications. This overview will equip readers with an essential framework of the concepts of psychopharmacology in an accessible length and style ideal for use as either a primer or refresher text.
Includes bibliographical references and index.
This edition also issued in print: 2020.
Specialized.
Description based on online resource; title from home page (viewed on September 10, 2020).
Keywords: Psychopharmacology; Psychotropic drugs